Comparison of nutrient intake and digestibility, rumen fermentation along with body weight gain in cattle and buffalo fed maintenance diet - DAS, P; DEVALIA, B R; SHEKH, M A; LUNAGARIYA, P M; WADHWANI, K N; SARVAIYA, N P (The Indian Journal of Animal Sciences, 2022)
In the present study, feed and nutrient intake, body weight changes, nutrient digestibility and rumen fermentation parameters were compared in cattle and buffaloes. Seven cattle (T1) and seven buffaloes (T2) were placed in two groups based on body weight employing completely randomized design. Experimental feeding in the form of total mixed ration (TMR) was carried out for 75 days having concentrate (C) and roughage (R) in 30C:70R. The daily intake of dry matter, crude protein, digestible crude protein and total digestible nutrients was non-significant between cattle and buffaloes. While in terms of percentage and metabolic body weight, the same parameters were significantly lower in cattle compared to buffalo. Digestibility of DM, OM, CP, EE, CF, NFE, NDF and ADF marginally differed between cattle and buffaloes. Rumen liquor pH, ammonia, non-protein and soluble nitrogen concentration was non-significantly different between cattle and buffaloes with significant lower value of total volatile fatty acids (12.25 vs. 14.19 mM/dl), total nitrogen (90.53 vs. 101.73 mg/dl) and TCA precipitable nitrogen (51.33 vs. 61.36 mg/dl) in cattle compared to buffaloes. Thus, from the study, it may be concluded that under similar feed and managemental conditions, intake of dry matter and nutrients per unit of body weight was lower, with non-significant difference in nutrients digestibility and inferior nitrogen fermentation as observed in cattle than buffaloes.